Selective lithium leaching from dolomite-hosted clay-based boron extraction waste with oxalic acid to obtain a pregnant solution with a low Mg/Li ratio - Aladag, Merve; Erdem, Mehmet (Elsevier, 2025)
Production of lithium from lithium sources such as minerals and brines with high magnesium content is the most challenging problem due to their similar ionic properties. To overcome this difficulty, selective solvent use, and additional extraction or purification methods are needed. Dolomite-hosted clay-based boron extraction waste, which is released in significant amounts in boron production, is also a potential lithium source due to its high lithium content. However, it is necessary to break the mineral structures by dissolving them to recover the lithium trapped in the clay and dolomite structure. In this study, lithium leaching from the boron waste has been investigated using oxalic acid, which will destroy the dolomite and clay structure with its protons and precipitate calcium and magnesium in the solution with its anions, thus providing a pregnant solution with lower Mg/Li content. 99.92 % of lithium was leached and a pregnant solution with a Mg/Li ratio of 0.033 was obtained under the optimized conditions. The leaching mechanism was investigated through chemical, mineralogical, and morphological tests and heterogenous kinetics models. The leaching kinetics was found to fit the shrinking core heterogeneous kinetics model controlled by chemical reactions on the particle surface and the activation energy was 53.971 kJ/mol.
Keywords: Lithium recovery; Leaching; Boron waste; Resource recycling; Heterogeneous kinetics; Oxalic acid